2020
DOI: 10.1042/bst20190282
|View full text |Cite
|
Sign up to set email alerts
|

From diagnosis to therapy in Duchenne muscular dystrophy

Abstract: Genetic approaches for the diagnosis and treatment of inherited muscle diseases have advanced rapidly in recent years. Many of the advances have occurred in the treatment of Duchenne muscular dystrophy (DMD), a muscle wasting disease where affected boys are typically wheelchair bound by age 12 years and generally die in their twenties from respiratory failure or cardiomyopathy. Dystrophin is a 421 kD protein which links F-actin to the extracellular matrix via the dystrophin-associated protein complex (DAPC) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 41 publications
0
15
0
10
Order By: Relevance
“…Recently several novel therapies targeting specific DMD mutations (including stop-codon read-through agents, exonskipping antisense oligonucleotides (AONs) etc.) that target and restore Dystrophin function (Aartsma-Rus et al, 2009;Babbs et al, 2020;Haas et al, 2015;Laing et al, 2011;Ousterout et al, 2015;Reinig et al, 2017) have been developed. An early and accurate molecular diagnosis is critical for most of these therapies (Aartsma-rus et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recently several novel therapies targeting specific DMD mutations (including stop-codon read-through agents, exonskipping antisense oligonucleotides (AONs) etc.) that target and restore Dystrophin function (Aartsma-Rus et al, 2009;Babbs et al, 2020;Haas et al, 2015;Laing et al, 2011;Ousterout et al, 2015;Reinig et al, 2017) have been developed. An early and accurate molecular diagnosis is critical for most of these therapies (Aartsma-rus et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Since the first attempt by Howard and colleagues in 1996 [ 64 ], several relevant diseases have been challenged with this correction strategy, including Duchenne/Becker dystrophy [ 68 , 114 , 115 , 116 , 117 , 118 ], cystic fibrosis [ 119 , 120 , 121 , 122 , 123 , 124 ], and spinal muscular atrophy [ 84 , 125 , 126 ]. Broad information on the efficacy of drug-induced readthrough for these disease models, as well as a detailed discussion on readthrough -inducing compounds, have been recently reviewed [ 87 , 127 , 128 , 129 ]. In addition, further details on approaches related to stop codon suppression or other strategies for the correction of molecular defects in genetic disorders have also been described [ 130 , 131 , 132 ].…”
Section: Implications For a Nonsense Suppression Approachmentioning
confidence: 99%
“…More recently, research has focused on possible gene-based strategies, and a few of these are now reaching the phase II/III clinical trial stage. They include, among others, upregulation of utrophin, enhancement of muscle regeneration, and virus-mediated minidystrophin gene therapy (www.clinicaltrials.gov; NCT03362502-accessed on 1 February 2021) [2]. Moreover, recently, the use of a group of cells called muscle side population (SP) cells to deliver genes, such as the human microdystrophin, showed that these SP cells are capable of recapitulating the myogenic lineage.…”
Section: Introductionmentioning
confidence: 99%